Keputusan Promosi Efektif dengan Metode Oreste Fuzzy Multiple Attribute Decision Making (FMADM) pada UMKM Gosimplywedding Sukabumi - Dicki Prayudi; Renny Oktapiani; Achmad Andika Gunawan (Teknik Informatika Universitas Pamulang, 2021)
Wedding Organizer is a service business for preparing wedding events. Since its establishment in 2015 to 2020, the Wedding Organizer in Sukabumi with the Gosimplywedding brand has carried out several sales methods to get clients, including Canvassing, Online Social Media, Internal Marketing, Marcomm Development, and Offline Shows. The Decision Support System required by management uses the FMADM method, in order to find the optimal alternative from a number of methods that have been used. The results of the calculation of Gosimplywedding sales data from 2017 to 2020 produced a method with Online Social Media in the first order with a value of 16 which is the smallest value ranking. This method is considered the most effective and most generates brand sales so that it can be used as a decision by management for the following year.